Alternative investment market and the performance of nominated advisers. - Chen, Guozheng. (2008)
This project investigates the performance of nominated advisers (nomads) in terms of the stock price performance of the companies listed on the Alternative Investment Market (AIM). Indices for the respective nomads were constructed. Comparisons were made on the returns and returns volatility of the indices for different categories of nomads.